Sosialisasi Pemberdayaan Masyarakat Guna Pencegahan Pernikahan Dini di Desa Candi, Kecamatan Dungkek - Nindhita, Vidya; Fauzan, Ahmad; Putri, Ivon Valentina; Saputra, Wahyu Aril (Jurnal Solutif: Jurnal Pengabdian Masyarakat, 2024)
Early marriage is a marriage performed by a minor in accordance with Law No 16 of 2019, which states that the age of a child is 19 years. As in Candi Village, Dungkek Subdistrict, Sumenep District, the number of early marriages is still a problem that has not been resolved by village government officials. Moreover, there are many negative impacts of early marriage. Therefore, the program proposed in this community service aims to help village officials and assist the community in understanding the dangers of early marriage. The method used in village community service is mentoring and counseling delivered directly by the mentoring team. The results of the community service program show that the community enthusiastically welcomes the material presented, and village officials are very concerned about efforts to reduce the problem of early marriage in Candi village.